2016
DOI: 10.1111/scs.12346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extended childbirth education by midwives on the childbirth fear of first‐time mothers: an RCT

Abstract: The effectiveness of the intervention can be considered moderate: one of three objects and one of three manifestations of fears were reduced. The intervention proved most efficient in alleviating relatively limited objects of fears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 29 publications
2
51
0
6
Order By: Relevance
“…Çalışmada doğum hakkında bilgi düzeyi yüksek olan gebelerin çok düşük de olsa doğumdan daha az korktukları saptandı (p<0,05). Yurt dışında yapılmış çalışmalarda doğum önce si eğitimin doğum korkusunu düşürdüğü tespit edilmiştir (46,47). Ülkemizde yapılan çalışmalarda da benzer şekilde doğum öncesi verilen eğitimin doğum korkusunu azalttığı, kendi kendine yeterliliğe ve ailesel bağlanmada artmaya neden olduğu belirlenmiştir (14,48,49).…”
Section: Yöntemunclassified
“…Çalışmada doğum hakkında bilgi düzeyi yüksek olan gebelerin çok düşük de olsa doğumdan daha az korktukları saptandı (p<0,05). Yurt dışında yapılmış çalışmalarda doğum önce si eğitimin doğum korkusunu düşürdüğü tespit edilmiştir (46,47). Ülkemizde yapılan çalışmalarda da benzer şekilde doğum öncesi verilen eğitimin doğum korkusunu azalttığı, kendi kendine yeterliliğe ve ailesel bağlanmada artmaya neden olduğu belirlenmiştir (14,48,49).…”
Section: Yöntemunclassified
“…4,6,10 In Finland study reported that pregnant women in antenatal education group had less fear of childbirth than those in the control group. 9 Fabian and colleagues reported that the majority of women (74%) found antenatal education classes helpful in preparing for childbirth and early parenthood. 8 Pregnant education classes may have been effective in reducing fears, because it provides knowledge and skills about pregnancy, childbirth and postpartum process.…”
Section: Discussionmentioning
confidence: 99%
“…26 Haapio and colleagues stated that the most common fear related to childbirth and the child's and mother's well-being. 9 In a longitudinal cohort study of 2541 Swedish women, 70% of women had a negative birth experience that risk factors were related to emergency cesarean section, pain and loss of control. 25 In Sweden study reported that some women with low fear of childbirth had the most positive birth experience, but others women with high fear of childbirth had a negative birth experience and underwent emergency cesarean section and instrumental vaginal delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations